Triple Helix: a sustainable economy for hijab SMEs in the new normal - Jun Surjanti; Tony Seno Aji; Sanaji Sanaji; Setya Chendra (Jurnal Siasat Bisnis, 2021)
Although the COVID-19 pandemic has gradually improved, people's activities have not recovered to normal due to various conditions. This period is a transition period known as the "New Normal". Besides its impact on people's health, COVID-19 also affects other aspects, including the economy, education, and law. The economic impact highly touches low-medium class people including SMEs as the business activities which need to be halted due to PSBB (Large-Scale Social Restriction). Triple Helix is a SMEs' development model that links Science (S), Government (G), and Business (B). This article aims to examine whether Triple Helix with SGB Balanced model is possibly utilized to revive the Hijab SMEs business activity. This study is descriptive-qualitative research and analyzed using the Miles and Hubberman techniques. Data were obtained through online questionnaires and interviews from hijab craftsmen associating with two SMEs. The results show that respondents have successfully adapted to the New Normal and resumed their business activity by implementing technology and information given by the S (science) agent and the G (government) agent’s assistance. Therefore, it indicates that implementing Triple Helix provably revives the Hijab SMEs business activities.